Underactive Bladder; Review of Progress and Impact From the International CURE-UAB Initiative - Chancellor, Michael B.; Bartolone, Sarah N.; Lamb, Laura E.; Ward, Elijah; Zwaans, Bernadette M.M.; Diokno, Ananias (International neurourology journal, 2020)
There is a significant need for research and understanding of underactive bladder (UAB). The International Congress of Urologic Research and Education on Aging UnderActive Bladder (CURE-UAB) was organized by Doctors Michael Chancellor and Ananias Diokno in order to address these concerns. CURE-UAB was supported, in part, by the US National Institute of Aging and National Institute of Diabetes Digestive and Kidney. Since 2014, there have been 5 successful CURE-UAB congresses. They have brought together diverse stakeholders in the UAB field to identify areas of major scientific challenge and initiated a call to action among the medical community. In this review, we will highlight current and novel treatments under development for UAB and the progress and impact from the CURE-UAB initiative.